Biochemical Evaluation of Bone Health in Children with Phenylketonuria, Organic Acidemias, and Glycogen Storage Diseases Under Dietary Management - Sabire Gokalp; Hatice Pasaoglu (Nutrients, 2026)
Background: Inherited metabolic disorders (IMDs) are a heterogeneous group of genetic diseases, some of which require lifelong disease-specific dietary management. Children with phenylketonuria (PKU), organic acidemias (OAs), and glycogen storage diseases (GSDs) are particularly susceptible to nutritional imbalances and metabolic disturbances that may adversely affect bone metabolism and skeletal health. However, data regarding bone turnover markers and bone health in these pediatric IMD populations remain limited. Objective: This study aimed to evaluate bone metabolism by assessing biochemical parameters, bone turnover markers, and bone mineral density in children with PKU, OA, and GSD receiving long-term dietary treatment. Methods: This cross-sectional study included 95 children, comprising 25 patients with PKU, 20 patients with organic acidemias, 20 patients with glycogen storage diseases, and 30 healthy age-matched controls. Demographic characteristics, anthropometric measurements, and dietary intake were recorded. Biochemical evaluation included serum calcium, phosphorus, alkaline phosphatase (ALP), parathyroid hormone (PTH), and 25-hydroxyvitamin D levels. Bone turnover was assessed using C-terminal telopeptide of type I collagen (CTX), procollagen type I N-terminal propeptide (P1NP), and osteocalcin (OC) levels. Bone mineral density was evaluated by dual-energy X-ray absorptiometry (DXA). Results: Age and sex distributions were similar among the groups. Height was lower in OA than in controls and PKU, and in GSD than in PKU; weight and BMI were lower in both OA and GSD than in controls and PKU (p < 0.05). Significant differences were observed in dietary energy and macronutrient intake according to disease-specific nutritional regimens. Serum calcium, phosphorus, and 25-hydroxyvitamin D levels were significantly lower in all IMD groups compared with healthy controls (p < 0.001). ALP and PTH levels were significantly higher in PKU, OA, and GSD patients than in controls (p < 0.001). Among bone turnover markers, P1NP and osteocalcin levels significantly differed among groups, with the highest values observed in PKU patients (p = 0.006 and p = 0.028, respectively). CTX levels did not significantly differ among the groups (p = 0.183). DXA Z-scores were significantly lower in all IMD groups than in controls, with the lowest mean Z-scores observed in GSD patients. Conclusions: Children with PKU, OA, and GSD receiving long-term dietary treatment exhibited significant alterations in bone metabolism, characterized by lower vitamin D, calcium, and phosphorus levels, higher ALP and PTH concentrations, differences in bone formation markers, and lower DXA Z-scores compared with controls. Significant differences were observed in the bone formation markers P1NP and osteocalcin, whereas CTX levels remained comparable among the study groups. These findings underscore the importance of regular assessment of bone health and optimization of nutritional management in children under dietary treatment, while acknowledging that disease-specific mechanisms of skeletal involvement may differ among these conditions.